2001
DOI: 10.1001/archopht.119.6.875
|View full text |Cite
|
Sign up to set email alerts
|

Association of Demographic, Familial, Medical, and Ocular Factors With Intraocular Pressure

Abstract: To describe the distribution and associations of demographic, familial, medical, and ocular factors with intraocular pressure (IOP). Methods: A cluster stratified random sample of urban and rural residents of Victoria, Australia, aged 40 years and older. Participants completed an interview and underwent a standardized dilated ophthalmic examination including measurement of IOP with an electronic applanation tonometer (Tono-Pen). Glaucoma status (possible, probable, definite) was determined by a consensus panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 22 publications
3
63
2
4
Order By: Relevance
“…This may be explained by much lower expression of mutated Myoc in the TM of Tg animals compared with the in vitro studies. Interestingly, our experiments demonstrated increased occurrence of apoptotic cell death in tissues surrounding the TM (our un- Many studies demonstrated that there is a correlative relationship between glaucoma and IOP elevation (Weih et al, 2001;Kass et al, 2002). We observed moderate elevation of IOP by ϳ2 mmHg in both eyes of Tg mice compared with Wt littermates.…”
Section: Discussionmentioning
confidence: 52%
“…This may be explained by much lower expression of mutated Myoc in the TM of Tg animals compared with the in vitro studies. Interestingly, our experiments demonstrated increased occurrence of apoptotic cell death in tissues surrounding the TM (our un- Many studies demonstrated that there is a correlative relationship between glaucoma and IOP elevation (Weih et al, 2001;Kass et al, 2002). We observed moderate elevation of IOP by ϳ2 mmHg in both eyes of Tg mice compared with Wt littermates.…”
Section: Discussionmentioning
confidence: 52%
“…[17][18][19] In addition to the environmental effect, genetic factors may explain these differences. 20 In addition, this study found that the degree of IOP change was different depending on the age group. The correlation coefficient was − 0.260 in the 20s~30s age groups and − 0.168 in the 60s~80s age group, implying that IOP of old age groups was less decreased than that of younger groups (Table 2).…”
Section: Discussionmentioning
confidence: 72%
“…11,12 Schulzer and Drance found that adjustment for systolic blood pressure accounted for any age effect. 13 Consistent associations with increasing IOP have been reported for increasing systolic blood pressure, 5,7,8,10,12,16,17 darker iris color, 9,14,18 and myopia. 6,14,18 Once glaucoma is diagnosed and treatment is initiated, the influence on IOP attributable to demographic, systemic, and ocular factors might be overwhelmed by the impact of glaucoma treatment.…”
Section: Introductionmentioning
confidence: 72%